Judges: a critical and rhetorical commentary - Nelson, Richard D. (Bloomsbury Publishing, 2017)
List of Abbreviations -- Introduction -- Judges 1 -- Judges 2 -- The Cyclical Framework -- Judges 3 -- Judges 4 -- Judges 4 and the Song of Deborah -- Judges 5 -- Judges 6 -- Judges 7 -- Judges 8 -- Judges 9 -- Judges 10 -- Judges 11 -- Judges 12 -- Judges 13 -- Judges 14 -- Judges 15 -- Judges 16 -- Judges 17 -- Judges 18 -- Judges 19 -- Judges 20 -- Judges 21 -- Judges 17-21 as Epilogue